Sleep deprivation and recovery sleep affect healthy male resident’s pain sensitivity and oxidative stress markers: The medial prefrontal cortex may play a role in sleep deprivation model - Chen, Shuhan; Xie, Yanle; Li, Yize; Fan, Xiaochong; Xing, Fei; Mao, Yuanyuan; Xing, Na; Wang, Jingping; Yang, Jianjun; Wang, Zhongyu; Yuan, Jingjing (Frontiers in Molecular Neuroscience, 2022)
Sleep is essential for the body's repair and recovery, including supplementation with antioxidants to maintain the balance of the body's redox state. Changes in sleep patterns have been reported to alter this repair function, leading to changes in disease susceptibility or behavior. Here, we recruited healthy adult physicians and measured the extent of the effect of overnight sleep deprivation (SD) and recovery sleep (RS) on nociceptive thresholds and systemic (plasma-derived) redox metabolism, including the major antioxidants glutathione (GSH), catalase (CAT), malondialdehyde (MDA), and superoxide dismutase (SOD). Twenty subjects (n=20, μ age 26 years, SD=2) underwent morning measurements before and after overnight total SD and RS. We found that one night of SD can lead to increased nociceptive hypersensitivity and the Numerical Rating Scale (NRS) pain scores, and that one night of RS can reverse this change. Pre- and post-SD biochemical assays showed an increase in MDA levels and CAT activity, a decrease in GSH levels and SOD activity after overnight SD. Biochemical assays before and after RS showed a partial recovery of MDA levels and a basic recovery of CAT activity to baseline levels. Animal study showed that SD can cause a significant decrease in the paw withdraw threshold and paw withdraw latency in rats, after 4 days of unrestricted sleep, pain thresholds can be restored to normal. Current findings have shown that SD causes nociceptive hyperalgesia and oxidative stress, and that RS can restore pain thresholds but only partially repair oxidative stress damage in the body.